2017
DOI: 10.1016/j.ijar.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Repairing inconsistent answer set programs using rules of thumb: A gene regulatory networks case study

Abstract: Answer set programming is a form of declarative programming that can be used to elegantly model various systems. When the available knowledge about these systems is imperfect, however, the resulting programs can be inconsistent. In such cases, it is of interest to find plausible repairs, i.e. plausible modifications to the original program that ensure the existence of at least one answer set. Although several approaches to this end have already been proposed, most of them merely find a repair which is in some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Furthermore, the proposed tool currently produces all the optimal solutions given the defined optimisation criteria. Heuristics to filter the produced output could also be considered, in particular those proposed in the work of Merhej et al (2017) where rules of thumb are discussed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, the proposed tool currently produces all the optimal solutions given the defined optimisation criteria. Heuristics to filter the produced output could also be considered, in particular those proposed in the work of Merhej et al (2017) where rules of thumb are discussed.…”
Section: Resultsmentioning
confidence: 99%
“…Most approaches define atomic repair operations and minimise the number of operations applied to render a model consistent. Merhej et al (2017) proposed the use of rules of thumbs, which are properties found in the literature, in order to repair inconsistent Boolean models. This work considers Boolean models where the regulatory function of each compound is as follows: it becomes active if there is at least one active activator and there is no active inhibitor; it becomes inactive if there is at least one active inhibitor and there is no active activator; otherwise its value is not changed.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations